Rancang Bangun Layanan Kesehatan dan Keselamatan Kerja Go-Health Untuk Klinik Perusahaan - Iwan Hermawan S; Aldo Okta Fernando; Rohmat Rifai; Kursehi Falgenti (Journal of Applied Computer Science and Technology, 2021)
Occupational health and safety services must be provided by the company as regulated in government regulations. To make it easier for companies to provide occupational health and safety services, cloud-based services are needed that can be accessed from various devices. In contrast to public health services, company health services are required to provide work safety reports. The purpose of developing this service is to help employees get effective health services, make it easier for medical personnel to provide health services, avoid queues, shorten health service times and make it easier for companies to get occupational health and safety reports. The research method used is direct observation and system development using the waterfall method. Health services in the form of an online information system application can provide benefits for employees to facilitate consulting services and purchasing drugs. While the benefits for the company as risk control related to work activities. To create a safe, efficient and productive workplace. The results of this health service design are service prototypes that have been tested. With the support of this cloud-based service, it is easier for employees to be based on Android by taking advantage of the shortcomings of the existing system in the company.